A Screening Method for the Isolation of Polyhydroxyalkanoate-Producing Purple Non-sulfur Photosynthetic Bacteria from Natural Seawater - Higuchi-Takeuchi, Mieko; Morisaki, Kumiko; Numata, Keiji (Frontiers in Microbiology, 2016)
Polyhydroxyalkanoates (PHAs) are a family of biopolyesters accumulated by a variety of microorganisms as carbon and energy storage under starvation conditions. We focused on marine purple non-sulfur photosynthetic bacteria as host microorganisms for PHA production and developed a method for their isolation from natural seawater. To identify novel PHA-producing marine purple non-sulfur photosynthetic bacteria, natural seawaters were cultured in nutrient-rich medium for purple non-sulfur photosynthetic bacteria, and twelve pink- or red-pigmented colonies were picked up. Gas chromatography mass spectrometry analysis revealed that four isolates synthesized PHA at levels ranging from 0.5 to 24.4 wt% of cell dry weight. The 16S ribosomal RNA sequence analysis revealed that one isolate (HM2) showed 100% identity to marine purple non-sulfur photosynthetic bacteria. In conclusion, we have demonstrated in this study that PHA-producing marine purple non-sulfur photosynthetic bacteria can be isolated from natural seawater under nutrient-rich conditions.